Proximal Anterior Cruciate Ligament Tear Primary Repair Using a Tensionable Knotless Anchor System - German Alejandro Jaramillo Quiceno, M.D.; Paula Andrea Sarmiento Riveros, M.D.; Rubén Darío Arias Pérez, B.S., M.D.; Andrés Julián Mesa Bravo, M.D. (Arthroscopy Techniques, 2025)
Recently, there has been a growing interest in repairing proximal anterior cruciate ligament (ACL) tears, a technique gaining popularity for its outcomes comparable with reconstruction methods within certain population subsets. Although many techniques have been described, it is difficult to reach a definitive consensus on the most effective approach. As a result, a surgical technique is presented to optimize the repair technique. In this procedure, the proximal bundles of the ACL are sutured using lasso-loop stitches, and a transosseous femoral tunnel is made to facilitate the passage of suture threads, which are subsequently fixed using a tension-control knotless suture anchor to the lateral femoral cortex, all arthroscopically. This surgical method not only allows for accurate tensioning during fixation but also reduces the possibility of interference with the healing process by eliminating the presence of implants in the femoral footprint and increasing the ligament-bone contact area. The meticulous control of ACL tension, along with the lack of implants in the footprint, contributes to a more efficient and undisturbed ligament healing process within the femur.